Renewable energy innovations and sustainability transition: How relevant are spatial spillovers?. (3rd April 2017) - Noseleit, Florian
Abstract: In the societal challenge to switch to renewable energy, innovation has become an ever‐increasing critical determinant. However, while sustainability transition is a global challenge, diffusion and adoption of innovation tends to be uneven in space and unequal access may cause substantial heterogeneity in energy transition. This research analyzes how domestic and foreign innovation activities in the renewable energy sector influence energy transition over time. Empirical testing shows that a country's domestic innovation activity impacts renewable electricity generation capacity sooner than foreign technological innovations. I document that there are substantial barriers to substitute foreign technologies for domestic innovation efforts in the short run but also observe that foreign technologies have a stronger impact after some years. These findings have implications for cross‐border coordination of governmental innovation support and complementary policy instruments that aim at increasing adoption speed across borders.